1999
DOI: 10.1063/1.371131
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental responses for a large-aperture broadband spherical transducer probing a liquid–solid boundary

Abstract: A theoretical analysis of a spherical focusing transducer for broadband acoustic microscopy is proposed. The originality of the present contribution is the particular attention we have paid to describe, as rigorously as possible, the diffraction phenomena. Our analysis starts in the harmonic domain with the well-known angular spectrum method, and then gets into the time domain. A new formulation of the angular spectrum in the focal plane has been obtained and compared to other expressions previously reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It has been shown in ref. [10] that the GEW contributions are noticeably larger than those of the direct wave. The same observations were made for the case of non-confocal transmission microscopy in [7].…”
Section: Non-confocal Transmission Psammentioning
confidence: 85%
See 1 more Smart Citation
“…It has been shown in ref. [10] that the GEW contributions are noticeably larger than those of the direct wave. The same observations were made for the case of non-confocal transmission microscopy in [7].…”
Section: Non-confocal Transmission Psammentioning
confidence: 85%
“…This amplitude peak was identified in [7] to be due to "edge-to-focus" waves. They were termed Geometrical Edge Waves (GEW) by Zhang et al in [10] and Fig. 3 Travel paths for "straight edge-to-edge" (dashed line), "diagonal edge-to-edge" (dot-dashed line), "edge-to focus" (dotted line), and "direct" waves (solid line), obeying ray acoustics rules.…”
Section: Non-confocal Transmission Psammentioning
confidence: 99%
“…(14). However, computational methods allow for the numerical modeling of the propagating short acoustic pulses in TRSAM [59,60]. Schubert et al reported the numerical simulation of the acoustic pulse propagation and reflection of the focusing incident waves for different types of scatterers using the elasto-dynamic finite integration technique (EFIT) [61].…”
Section: Theory Of Time-resolved Acoustic Microscopymentioning
confidence: 99%
“…1,2 The recent trend toward micro-and nano-technologies demands higher resolution and also cross-sectional images with higher signal-tonoise ratio in advanced samples, e.g., microelectronic packages. [3][4][5] Pushing the operating frequency of acoustic devices up to the gigahertz range, and also the realization of broadband ultrasound, 6 have been shown to be effective in improving spatial resolution, and sometimes the resolution that can be achieved is superior to that of an optical microscope. 7,8 However, the penetration depth of the highfrequency components of ultrasound is shallow, and the area that can be evaluated is limited to only the surface or the subsurface.…”
Section: Introductionmentioning
confidence: 99%